A method for preparing a high-energy dense silicon-carbon negative electrode material with extremely low volume expansion
By using the structure of mesoporous and porous carbon in the negative electrode material of lithium-ion battery, the ratio of micropores and mesoporous is controlled, the problem of high volume expansion of silicon-carbon composite materials in lithium-ion batteries is solved, and a high energy density and low expansion material preparation is achieved.
Patent Information
- Application Number
- CN202411894510.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
AI Technical Summary
The existing silicon-carbon composite anode materials have high volume expansion problems in lithium-ion batteries, resulting in poor cycle stability and electrochemical performance.
The structure of mesoporous and porous carbon is adopted to prepare silicon-carbon composite materials through the fluidized bed method, and the ratio of micropores and mesoporous is controlled, with a micropore ratio of 40-70% and a mesoporous ratio of 30-60% to reduce the filling rate of nanosilicon and reserve space for volume expansion.
A high-energy dense silicon carbon negative electrode material with extremely low volume expansion is achieved, which improves the cyclic stability and electrochemical performance of the material and reduces the expansion of the electrode sheet level.
Smart Images

Figure CN119764382A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of silicon-carbon negative electrode materials, and in particular to a method for preparing a high-energy-dense silicon-carbon negative electrode material with extremely low volume expansion. Background Art
[0002] In the field of lithium-ion batteries, silicon-carbon composite anode materials have attracted much attention due to their high theoretical capacity. However, silicon anode materials have significant volume expansion problems during the charge and discharge process, which limits their cycle stability and practical applications. To address this problem, researchers have developed a variety of silicon-carbon composite structures, aiming to buffer the volume expansion of silicon by introducing a porous carbon matrix and improve the electrochemical performance of the overall material.
[0003] The traditional chemical vapor deposition (CVD) method is widely used to prepare silicon-carbon composite materials because it can accurately control the deposition process of silicon. However, the existing CVD silicon-carbon materials still have challenges in the design of microporous structures. The shortcomings of the existing technology are as follows:
[0004] CVD silicon-carbon high volume expansion: In the prior art, for example, patent announcement number: CN117577819A developed a silicon-carbon composite negative electrode material and its preparation method and application. This highly compact composite structure greatly improves the cycle and expansion of silicon negative electrode materials. However, the silicon-carbon material based on this structure still cannot meet the requirements of the battery cell end for the expansion rate. The presence of micropores provides high energy sites and high specific surface area, and has a strong adsorption capacity for silane molecules, but the excessive adsorption capacity leads to saturation of nano-silicon in the pores. The insufficient space reserved in the pores makes it impossible for the particles to fully absorb the volume deformation stress of nano-silicon during lithium insertion. After the lithium insertion cycle, the interface thickens and even the particles disintegrate, which leads to the shedding of active substances and the attenuation of the battery cycle performance.
[0005] CVD mesoporous silicon carbon gas production: Data show that mesoporous silicon carbon can improve the initial efficiency and rate performance of the material to a certain extent, but the introduction of mesopores reduces the adsorption capacity of porous carbon itself to silane gas, resulting in a higher specific surface area of the material, which further causes a series of problems such as gas production.
[0006] In view of this, there is an urgent need for a preparation method of a high-energy dense silicon-carbon negative electrode material with extremely low volume expansion to address the deficiencies of the prior art. Summary of the invention
[0007] The object of the present invention is to provide a method for preparing a high-energy dense silicon-carbon negative electrode material with extremely low volume expansion, so as to solve the problems raised in the above-mentioned background technology.
[0008] To achieve the above object, the present invention provides a method for preparing a high-energy dense silicon-carbon negative electrode material with extremely low volume expansion, comprising the following steps:
[0009] Step 1, placing porous carbon (mesoporous with porous carbon, wherein the microporosity is 40-70%, the mesoporosity is 30-60%, and the mesopore size is 2-5nm) into a fluidized bed, introducing nitrogen, and evacuating the exhaust gas at a nitrogen flow rate of 5L / min until the tail gas content is less than 100ppm, reducing the nitrogen flow rate to 1L / min, heating to 450°C at 5°C / min, and keeping warm for 30min, introducing 2L / min of monosilane into the fluidized bed cavity, using nitrogen as the carrier gas, and setting the whole flow rate to 10L / min. Preferably, the concentration of monosilane is 5-95%, and it is introduced for 200min;
[0010] Step 2: Reduce the flow rate of monosilane to 1 L / min and the flow rate of nitrogen to 8 L / min, and maintain for 300 min;
[0011] Step 3: Raise the temperature to 600-800°C, open acetylene, the acetylene flow rate is 1 L / min, and vapor precipitate for 2 hours to obtain a silicon-carbon composite material.
[0012] In the present invention, in silicon-carbon synthesis, the degree of the chamber filled with nano-silicon depends on the adsorption force of the porous carbon. For the adsorption of porous carbon, the higher the microporosity, the stronger the adsorption force. The mesopores have weak adsorption force and therefore cannot be completely filled. The introduction of mesopores can reduce the filling rate of nano-silicon in the mesopores, thereby reserving space for volume expansion and reducing the expansion of the electrode layer.
[0013] As a further improvement of the technical solution, the porous carbon matrix adopts one of biomass, coal-based, resin-based, and petroleum coke-based. Specifically, the porous carbon can be prepared by using coconut shells, coal, asphalt, phenolic resin, and rice husks.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] In the preparation method of the high-energy dense silicon-carbon negative electrode material with extremely low volume expansion, since the adsorption capacity of micropores is much greater than that of mesopores, the combination of micro-mesopores can realize the micropore adsorption and silicon filling, and the mesopores cannot be saturated with adsorption, so space is reserved, thereby alleviating the volume expansion of silicon during lithium insertion; the low flow rate in the early stage of silicon infiltration can appropriately increase the adsorption capacity of the mesopores for silane, and also fill a part of silicon in the mesopores to avoid physical isolation of the silicon material, which leads to obstruction of lithium ion diffusion; the high flow rate in the later stage accelerates the filling and closure of the pores and reduces the specific surface area of the material; secondly, the combination of micro-mesopores can completely control the reduction of the specific surface area of the material due to the presence of a certain amount of micropores, thereby avoiding processing risks. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Schematic diagram of the effect of changes in the microporosity of porous carbon according to an embodiment of the present invention. DETAILED DESCRIPTION
[0017] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0018] Example
[0019] The embodiment of the present invention provides a method for preparing a high-energy dense silicon-carbon negative electrode material with extremely low volume expansion, and the specific steps are as follows:
[0020] Step 1: Place porous carbon with a microporosity of 40% and a mesoporosity of 60% into a fluidized bed, introduce nitrogen, and evacuate the exhaust gas at a nitrogen flow rate of 5 L / min until the tail gas content is less than 100 ppm, reduce the nitrogen flow rate to 1 L / min, increase the temperature to 450°C at 5°C / min, and keep warm for 30 minutes. Introduce 2 L / min of monosilane into the fluidized bed cavity, use nitrogen as the carrier gas, set the flow rate to 10 L / min throughout the process, and introduce it for 200 minutes;
[0021] Step 2: Reduce the flow rate of monosilane to 1 L / min and the flow rate of nitrogen to 8 L / min, and maintain for 300 min;
[0022] Step 3: Raise the temperature to 600°C, open acetylene, the acetylene flow rate is 1 L / min, and perform vapor precipitation for 2 hours to obtain a silicon-carbon composite material.
[0023] In silicon-carbon synthesis, the degree of nanosilicon filling in the chamber depends on the adsorption force of porous carbon. For the adsorption of porous carbon, the higher the microporosity, the stronger the adsorption force, while the mesopores have weak adsorption force and therefore cannot be completely filled. Introducing mesopores can reduce the filling rate of nanosilicon in the mesopores, thereby reserving space for volume expansion and reducing the expansion of the electrode layer.
[0024] Example 2
[0025] Compared with Example 1, the microporosity of the porous carbon in step 1 is modified to 50%, and the mesoporosity is modified to 50%. The remaining steps are the same as those in Example 1 and will not be described in detail in this example.
[0026] Example 3
[0027] Compared with Example 1, the microporosity of the porous carbon in step 1 is modified to 60%, and the mesoporosity is modified to 40%. The remaining steps are the same as those in Example 1 and will not be described in detail in this example.
[0028] Example 4
[0029] Compared with Example 1, the microporosity of the porous carbon in step 1 is modified to 70%, and the mesoporosity is modified to 30%. The remaining steps are the same as those in Example 1 and will not be described in detail in this example.
[0030] In Examples 1-5 of the present invention, since the adsorption capacity of micropores is much greater than that of mesopores, the combination of micro-mesopores can realize the adsorption of silicon in the micropores, and the mesopores cannot be saturated with adsorption, so space is reserved, thereby alleviating the volume expansion of silicon when lithium is embedded; the low flow rate in the early stage of silicon infiltration can appropriately increase the adsorption capacity of the mesopores for silane, and also fill a part of silicon in the mesopores to avoid physical isolation of the silicon material, which leads to obstruction of lithium ion diffusion; the high flow rate in the later stage accelerates the filling and closure of the pores and reduces the specific surface area of the material; secondly, the combination of micro-mesopores can completely control the reduction of the specific surface area of the material due to the presence of a certain amount of micropores, thereby avoiding processing risks.
[0031] Comparative Example 1
[0032] Compared with Example 1, the microporosity of the porous carbon in step 1 is modified to 90%, and the mesoporosity is modified to 10%. The remaining steps are the same as those in Example 1, and will not be described in detail in this comparative example.
[0033] Comparative Example 2
[0034] Compared with Example 1, the microporosity of the porous carbon in step 1 is modified to 30%, and the mesoporosity is modified to 70%. The remaining steps are the same as those in Example 1, and will not be described in detail in this comparative example.
[0035] Table 1
[0036]
[0037]
[0038] According to Table 1 and Figure 1 It can be seen that the various properties of the silicon-carbon composite materials provided by Examples 1-4 of the present invention are better than those of Comparative Examples 1 and 2. The following is a detailed description of the comparison results:
[0039] (1) 1.5V capacity: The 1.5V capacities of Examples 2-4 and Comparative Example 1 are generally higher than that of Example 1, indicating that the capacity of the silicon-carbon negative electrode material increases with the increase in the microporosity of the porous carbon. Among them, the 1.5V capacity of Comparative Example 1 is the highest, reaching 1920mAh / g, while the 1.5V capacity of Example 4 is 1820mAh / g, which is also relatively high; this indicates that increasing the microporosity of the porous carbon helps to increase the capacity of the silicon-carbon negative electrode material.
[0040] (2) 1.5V first efficiency: The 1.5V first efficiency of Examples 2-4 and Comparative Example 1 is generally higher than that of Example 1, indicating that as the microporosity of porous carbon increases, the first efficiency of silicon-carbon negative electrode materials increases. The 1.5V first efficiency of Example 4 is the highest, reaching 93.5%, while the 1.5V first efficiency of Comparative Example 1 is 91.2%, slightly lower than that of Example 4; this indicates that within the range of microporosity of 40-70%, increasing the microporosity of porous carbon helps to improve the first efficiency of silicon-carbon negative electrode materials.
[0041] (3) Specific surface area: The specific surface areas of Examples 2-4 and Comparative Example 1 are generally lower than that of Example 1, indicating that the specific surface area of the silicon-carbon negative electrode material decreases with the increase of the microporosity of the porous carbon. The specific surface area of Comparative Example 1 is the lowest, only 1.3 m2 / g, while the specific surface area of Example 4 is slightly higher, 2.8 m2 / g; this indicates that increasing the microporosity of the porous carbon will lead to a decrease in the specific surface area of the silicon-carbon negative electrode material.
[0042] (4) Capacity retention rate after 100 cycles at 1C: The capacity retention rates after 100 cycles at 1C of Examples 2-4 and Comparative Example 1 are generally higher than that of Example 1, indicating that the cycle stability of the silicon-carbon negative electrode material is improved with the increase of the microporosity of the porous carbon. The capacity retention rate after 100 cycles at 1C of Example 4 is the highest, reaching 97.6%, while the retention rate of Comparative Example 1 is 97.2%, slightly lower than that of Example 4; this indicates that within the range of 40-70% microporosity, increasing the microporosity of the porous carbon helps to improve the cycle stability of the silicon-carbon negative electrode material.
[0043] (5) Expansion rate after 100 cycles: The expansion rates after 100 cycles of Examples 1-4 and Comparative Example 2 are generally lower than those of Comparative Example 1, indicating that within the range of 40-70% microporosity, increasing the microporosity of porous carbon helps to reduce the volume expansion of silicon-carbon negative electrode materials. The expansion rate after 100 cycles of Example 3 is the lowest, only 7.2%, while the expansion rate of Comparative Example 1 is the highest, reaching 22.7%; this indicates that when the microporosity is 60%, the volume expansion of the silicon-carbon negative electrode material is well suppressed.
[0044] (6) The microporosity of Comparative Example 2 is only 30%. However, due to the small number of micropores, the adsorption of silane by porous carbon is greatly reduced, the surface area cannot be reduced, and the expansion is aggravated by the floating silicon on the surface.
[0045] In summary, the comparison results of the embodiments and comparative examples show that increasing the microporosity of porous carbon within a certain range helps to improve the capacity, first efficiency, cycle stability, and reduce volume expansion of silicon-carbon negative electrode materials. However, when the microporosity is too high (such as 90% in comparative example 1), although the capacity and first efficiency are high, the volume expansion problem is still serious. Therefore, the microporosity of porous carbon in the present invention is adjusted to between 40-70%, which is an important factor affecting the high stability, high rate, and high cycle retention rate of silicon-carbon composite materials.
[0046] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a high-energy dense silicon-carbon negative electrode material with extremely low volume expansion, characterized in that: The following steps are involved: Step 1: Place porous carbon in a fluidized bed, introduce nitrogen, reduce the nitrogen flow rate and increase the temperature, introduce monosilane into the fluidized bed cavity, and use nitrogen as the carrier gas; Step 2, reducing the flow rate of monosilane; Step 3, heating up, opening acetylene, vapor precipitation, and obtaining a silicon-carbon composite material; The porous carbon has a microporosity of 40-70% and a mesoporosity of 30-60%.
2. The method for preparing a high energy dense silicon-carbon negative electrode material with extremely low volume expansion according to claim 1, characterized in that: The mesopore size of the porous carbon is 2-5 nm.
3. The method for preparing a high energy dense silicon-carbon negative electrode material with extremely low volume expansion according to claim 1, characterized in that: In the step 1, the nitrogen flow rate is 5 L / min to evacuate until the tail gas content is less than 100 ppm, the nitrogen flow rate is reduced to 1 L / min, the temperature is increased to 450° C. at 5° C. / min, and the temperature is kept for 30 minutes.
4. The method for preparing a high energy dense silicon-carbon negative electrode material with extremely low volume expansion according to claim 3, characterized in that: In the step 1, the flow rate of monosilane is 2 L / min, the whole flow rate is set to 10 L / min, and the flow time is 200 min.
5. The method for preparing a high energy dense silicon-carbon negative electrode material with extremely low volume expansion according to claim 4, characterized in that: In the step 2, the flow rate of monosilane was reduced to 1 L / min, and the flow rate of nitrogen was 8 L / min, which was maintained for 300 min.
6. The method for preparing a high energy dense silicon-carbon negative electrode material with extremely low volume expansion according to claim 5, characterized in that: In the step 3, the temperature is raised to 600-800° C., the acetylene flow rate is 1 L / min, and the vapor phase precipitation is performed for 2 hours.
7. The method for preparing a high energy dense silicon-carbon negative electrode material with extremely low volume expansion according to claim 1, characterized in that: The porous carbon matrix is one of biomass, coal, resin and petroleum coke.